Case report: A case of acute renal failure, rhabdomyolysis, and toxic encephalopathy associated with diquat poisoning in a pregnant woman - Li, Mengqin; Qin, Bao; Chen, Yuan; Cui, Yan; Hu, Ying Chun; Jiang, Zhi (Frontiers in Medicine, 2025)
We studied the case of a 22-year-old Pregnant woman who self-administered about 200 ml of diquat solution (200 g/L) during a suicide attempt. She developed vomiting, and was admitted to the emergency department of our hospital 5 h later. Based on symptoms, and elevated levels of myoglobin and creatine kinase, the patient was diagnosed with rhabdomyolysis, acute renal failure and toxic encephalopathy caused by diquat poisoning. Undergoing hemoperfusion and hemofiltration were administered immediately. Rhabdomyolysis, toxic encephalopathy, and abortion occurred successively in the pregnant woman. The patient was discharged from the hospital after 37 days of treatment with a Glasgow–Pittsburgh Cerebral Classification (CPC) score of grade 2.this was a case of diquat poisoning complicated with renal failure, rhabdomyolysis, and toxic encephalopathy in a pregnant, which would enrich the experience of diquat poisoning treatment.